Case report: Durable response after pembrolizumab in combination with radiation - induced abscopal effect in platinum - refractory metastatic endometrial clear cell carcinoma - Kao, Chien-Hsiang; Liu, Chien-Ting; Lin, Hao; Huang, Yung-Cheng; Lan, Jui; Ou, Yu-Che; Fu, Hung-Chun; Wu, Chen-Hsuan (Frontiers in Immunology, 2022)
Advanced endometrial clear cell carcinoma (CCC) tends to have poor prognosis owing to aggressive clinical behavior and poor response to conventional chemotherapy. Herein, we report a case of platinum-refractory recurrent ECCC successfully treated with the combination of pembrolizumab, localized radiotherapy and a few cycles of chemotherapy with an extremely durable response even after cessation of immunotherapy for 3 years at the time of publication.